Improving Students’ Vocabulary Mastery By Using Pictures At Seventh Grade Students Of SMP Makassar Raya - Nur Rahmah Wahyuddin (CV. Eureka Murakabi Abadi, 2022)
This research aimed at finding out whether or not pictures can improve students’ vocabulary mastery. Pre-experimental design was applied in this research with one group pretest- posttest design. The population of this research was seventh grade students of SMP Makassar Raya, academic year 2017/2018 which consisted of 3 classes. This research used simple random sampling. The samples were 28 students of 7A. The research instrument used vocabulary test consisted of word form, word meaning, and word use as the research instrument. The result of this research showed that the application of pictures can improve students’ vocabulary mastery. It was proved by the value of the t-test 31.09 which was greater than the value of t-table 1.70 the level of significance (p) = 0.05 and degree of freedom (n-1)=27.